We share the same struggle. Women in wales. Women in Nicaragua / Patricia Daniel - Daniel, Patricia (Nicaragua: Central America Group, 1998)
Why links between wales and the Atlantic Coast of Nicaruguan?, women all over striving for more participation, anyting is possible if your put your mind to it, Nicaraguan rite of passage, break the silence, say ´no´ to violence, enterprise and community, women in the countryside, country without language, country without heart, unity in deversity networking
Content, map, bibliography, illustrated cover
Col. Soc
Keywords: 1. WOMAN 2. WOMEN IN WALES 3. WOMEN IN NICARAGUA 4. SOCIOLOGY